131 The hypertensive response to exercise and cardiac abnormalities in male veteran endurance athletes. (17th July 2020) - Parry-Williams, Gemma; Merghani, Ahmed; Patel, Ayesha; Basu, Joyee; Miles, Christopher; MacLachlan, Hamish; Papadakis, Michael; Tome-Esteban, Maria Theresa; Sharma, Sanjay
Abstract : While the benefits of moderate regular exercise to overall health are irrefutable, there is a growing body of evidence to suggest that years of chronic endurance exercise may bear adverse cardiovascular consequences. A hypertensive response to exercise (HRE) has been correlated with adverse cardiovascular outcomes. We tested the hypothesis that the presence of a HRE in athletes who expose themselves to thousands of hours of endurance training may contribute to adverse structural and electrical cardiac remodelling, including pathological coronary calcification, myocardial fibrosis and ventricular arrhythmias. Between 2013-2015, 152 asymptomatic endurance athletes (70% male) and 92 controls of similar age (median 52; range 40-82 years) were evaluated with ECG, echocardiogram, cardiopulmonary exercise testing (CPET), 24 hour Holter monitoring, CT coronary angiography and cardiac MRI. Athletes with risk factors for coronary artery disease (CAD) were excluded. A HRE was defined as a peak systolic blood pressure during CPET of ≥220mmHg in males and ≥190mmHg in females. Data were analysed to evaluate for a significant relationship between the HRE and the presence of pathological coronary calcification (calcium score >70th Centile), myocardial fibrosis and ventricular tachycardia on 24hour Holter monitoring. Over a third of athletes (36.8%) compared to only 7.6% of controls exhibited a HRE on CPET testing (p<0.001). Athletes with a HRE did not differ in age (median 52), sex distribution, number of years of endurance training or hours of training per week compared to athletes without a HRE. Of the athletes with a HRE, 17.8% had pathological coronary calcification compared to 19.8% of athletes without (p=0.83), 12.7% had pathological myocardial fibrosis compared to 9.3% without (p=0.59) and 11% had non-sustained VT compared to 5.4% without (p=0.21). A hypertensive response to exercise is highly prevalent in veteran endurance athletes but present in only a minority of sedentary controls. The HRE, measured according to current methodology however, was not predictive for the presence of pathological coronary calcification, myocardial fibrosis or ventricular arrhythmias in this athlete cohort. Studies thus far are yet to explain the increased prevalence of such findings amongst veteran athletes or determine if such findings correspond to adverse cardiovascular events. Future studies should address these issues in order that evidence-based guidance for risk stratification and pre-participation screening of master athletes can be developed. Conflict of Interest: Nil